2017
DOI: 10.1007/s00268-017-4065-9
|View full text |Cite
|
Sign up to set email alerts
|

Caveolin‐1 is Markedly Downregulated in Patients with Early‐Stage Colorectal Cancer

Abstract: CAV-1 is commonly downregulated in patients with primary CRC, which suggests its tumor suppressor role in early stages of this disease. Moreover, based on our findings, the previous discrepancies observed in different studies to date could be due to a complex posttranscriptional CAV-1 regulation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 26 publications
2
6
0
Order By: Relevance
“…S 3e ). Although its role in metastasis formation is controversially discussed [ 55 ], there is evidence that CAV1 is decreased in early stages of carcinogenesis [ 56 , 57 ], but is found to be elevated at later stages [ 58 ], including in CRC [ 59 ]. Moreover, increased CAV1 expression in T4-stage CRCs was associated with increased invasiveness [ 60 ], and depletion of CAV1 reduced the invasive properties of human CRC cell lines [ 61 ].…”
Section: Resultsmentioning
confidence: 99%
“…S 3e ). Although its role in metastasis formation is controversially discussed [ 55 ], there is evidence that CAV1 is decreased in early stages of carcinogenesis [ 56 , 57 ], but is found to be elevated at later stages [ 58 ], including in CRC [ 59 ]. Moreover, increased CAV1 expression in T4-stage CRCs was associated with increased invasiveness [ 60 ], and depletion of CAV1 reduced the invasive properties of human CRC cell lines [ 61 ].…”
Section: Resultsmentioning
confidence: 99%
“…The roles of Cav-1 in cancers are controversial. In some cancers, such as colorectal cancer [17] and ovarian cancer [18], Cav-1 expression is down-regulated, suggesting that Cav-1 can inhibit such cancer development. Interestingly, it is elevated in other malignancies such as endometrial carcinoma [19], hepatic cancer [20], breast cancer [21], prostate cancer [21], and pancreatic cancer [22], in which Cav-1 propels cell growth and migration and results in cancer deterioration.…”
Section: Overview Of Caveolae and Cav-1mentioning
confidence: 99%
“…The CAV-1 gene is related to cell metastasis and has been confirmed to play a role in numerous tumors. Torrejón et al confirmed that the expression of CAV-1 in patients with colorectal cancer is usually down-regulated, and exerts a tumor suppressor effect in the early stages of the disease (14). Similarly, CAV-1 also exerts a tumor suppressor effect in breast and ovarian cancers (15,16).…”
Section: Discussionmentioning
confidence: 96%